EFFICIENCY OF SHARIA INSURANCE COMPANIES IN INDONESIA, A DATA ENVELOPMENT ANALYSIS (DEA) APPROACH - Iyansyah Pratama Solehudin (Multidisciplinary Research Studies in Social Sciences, 2025)
The Sharia insurance industry in Indonesia has demonstrated robust growth, bolstered by increasing public literacy in Islamic finance. However, operational efficiency remains a critical challenge in achieving sustainable competitiveness. This study aims to assess the technical efficiency of Sharia insurance companies in Indonesia through a Data Envelopment Analysis (DEA) approach. The analysis includes eleven Sharia-compliant insurers—both general and life insurance units—over the period 2015 to 2019. An input-oriented DEA model with Variable Returns to Scale (VRS) was employed, using total assets, administrative expenses, and claims paid as inputs, and premium income along with investment income as outputs. The findings indicate that only a select few companies, such as Tokio Marine and Panindai-Ichi, consistently reached optimal efficiency levels. In contrast, firms like ACA and Prudential exhibited fluctuating and relatively low efficiency. Notably, 2017 marked the highest average efficiency across all companies. These insights highlight the need to optimize cost structures, adopt effective Sharia-compliant investment strategies, and advance operational digitalization to improve overall industry efficiency.Keywords: Efficiency, Sharia Insurance, Data Envelopment Analysis, DEA, Islamic Finance Industry